Kesantunan Tuturan Interogatif dalam Acara Online Media Gathering Dampak Covid-19 pada Petani Sawit RSPO dI Youtube - Marbun, Lusiana; Herwandi, Herwandi (UIR PRESS, 2021)
The objectives of this study are 1) to describe, analyze and interpret the interrogative speech contained in the online media gathering event of the impact of covid-19 on RSPO oil palm farmers on YouTube and 2) to describe, analyze and interpret the principles of politeness in every interrogative way at the event. online media gathering about the impact of covid-19 on RSPO oil palm farmers on youtube. This research is classified as a qualitative descriptive study. Data collection in this study is related to the following matters: 1) documentation techniques, 2) listening techniques, and 3) note taking techniques. Sources of data in this study are the speeches of presenters and resource persons, while the data in this study are interrogative speeches spoken by the emcees and speakers. In accordance with the problems in the study, namely, ordering, interrogative and maxim of the principle of politeness, the results of this are 1) by adding the word